THE STRUCTURE OF AMORPHOUS COPPER SULFIDE PRECIPITATES: AN X-RAY ABSORPTION STUDY - Pattrick R.A.D.; Mosselmans J.F.W.; Charnock J.M.; England K.E.R.; Helz G.R.; Garner C.D.; Vaughan D.J. (My University, 1997)
X-ray absorption (XAS) and X-ray photoelectron spectroscopy (XPS) analysis of copper sulfide precipitated from aqueous solution at ambient temperatures reveals the existence of a metastable primitive structure that ages to a structure with the characteristics of amorphous covellite; XAS provides direct structural information on the structure of these amorphous copper sulfides. Extended X-ray absorption fine structure (EXAFS) analysis of the primitive structure demonstrates the presence of disulfide (S2-groups) and a Cu-S interaction of 2.8 #9: the latter is not found in covellite. Copper K-edge X-ray absorption near-edge structure (XANES) indicates the dominance of 3- over 4-coordinate Cu in the primitive phase, while Cu L3-edge spectra reveal only Cu(I) to be present in all precipitates formed. XPS data confirm the presence of only Cu(I) and reveal that three types of S are present. Upon ageing, the primitive structure transforms to one with the characteristics of covellite, and this transformation involves the reordering of the S2- and Cu3S-CuS3-layers. Development of the primitive phase from either a wurtzite-like structure or planar Cu3S-CuS3-layers is possible, with the structural evolution driven by the antipathy of Cu(II) for tetrahedral coordination and anomalous electron densities in the metastable structures.